SISTEM INFORMASI PRODUKSI PADA KALIANDA FARM LAMPUNG SELATAN - Amin, M. Miftakul (IIB Darmajaya, 2011)
Kalianda farm is a company engaged in the cultivation of laying hens. Operational reporting daily transactions and daily, weekly and monthly are still using hand written. On the other hand, management needs to get a quick report to be presented on a periodic basis. As one effort to achieve these objectives, it is necessary to build an information system that can assist livestock operations in the data record Kalianda farm feed, egg production, administration, warehouse and generate reports. The system is built using technology that runs in a multiuser network of Local Area Network (LAN) architecture client / server applications that are expected to directly obtain information about the recapitulation in a relatively short time and has managed to periodically. Data collection instruments using library research, interviews, and documentation. While the software to build applications using MS. Visual Basic 6.0, MySQL and Crystal Reports 8.5. Of this study obtained a production information system with client / server architecture, so the application can be run by several users at the same time to assist the administration of farm production in Kalianda South Lampung. Keywords: Information Systems, Production